2021
DOI: 10.1038/s41467-021-26445-y
|View full text |Cite
|
Sign up to set email alerts
|

Giant charge-to-spin conversion in ferromagnet via spin-orbit coupling

Abstract: Converting charge current into spin current via the spin Hall effect enables efficient manipulation of magnetization by electrical current. However, its geometrical restriction is a serious obstacle to device applications because it prevents switching of perpendicular magnetization in the absence of an external field. To resolve this issue, ferromagnetic materials have attracted attentions because their time reversal asymmetry induces magnetic-dependent charge-to-spin conversion that removes this restriction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…We note this decrease in I th is observed in ST-FMR studies conducted on both 400 nm nanowire and 2 µm width strip samples, showing that it does not depend sensitively on sample geometry. It is thus possible that the spin current generated from the Py layer itself acts on the LAFO to increase the spin torques and reduce I th [39][40][41][42] ; previous studies have experimentally shown that spin-orbit torque can be generated from a single magnetic layer 19,43 . In addition, the edge mode can be dominant in hybrid devices and cause a moderelated change of nonlinear damping 44,45 , which would reduce radiative loss and thus reduce I th .…”
Section: Resultsmentioning
confidence: 99%
“…We note this decrease in I th is observed in ST-FMR studies conducted on both 400 nm nanowire and 2 µm width strip samples, showing that it does not depend sensitively on sample geometry. It is thus possible that the spin current generated from the Py layer itself acts on the LAFO to increase the spin torques and reduce I th [39][40][41][42] ; previous studies have experimentally shown that spin-orbit torque can be generated from a single magnetic layer 19,43 . In addition, the edge mode can be dominant in hybrid devices and cause a moderelated change of nonlinear damping 44,45 , which would reduce radiative loss and thus reduce I th .…”
Section: Resultsmentioning
confidence: 99%
“…When an out-of-plane polarized spin current J s flows into Mn 2 Au, σ z can be rotated to the in-plane y-axis (σ z × n direction) by the AFM moment (Néel vector) n (along the x-axis) at each spin sublattice (Figure 1a,c). [24,25] The alternating moments in two sublattices bring about opposite in-plane spins, leading to a shift of Fermi contours in the same direction for the two staggered spin sublattices, [26][27][28] thereby producing a charge current J c (Figure 1b,d). Benefiting from the SOC-related Néel-order field, the generated charge current is parallel to the Néel vector n. [26]…”
Section: Doi: 101002/adma202205988mentioning
confidence: 99%
“…The spin Hall angle was estimated to be the same order as that of Pt. In addition to that, it provides us a way to tune the spin-to-charge conversion efficiency [17][18][19] by varying the magnetization. Very recently, Leiva et al obtained a giant spin Hall angle about -0.19±0.04 in Weyl ferromagnetic Heusler compound Co 2 MnGa, which is among the highest reported for a ferromagnet.…”
Section: Introductionmentioning
confidence: 99%